Fifty-fifty - a comparison of two 50 watts high power short duration protocols using temperature- versus power- controlled radiofrequency ablation for atrial fibrillation. (19th May 2022) - Guckel, D; Bergau, L; Braun, M; El Hamriti, M; Lucas, P; Isgandarova, K; Fink, T; Sciacca, V; Khalaph, M; Imnadze, G; Sommer, P; Sohns, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Radiofrequency-guided catheter ablation (RFCA) is an established treatment option for atrial fibrillation (AF). New approaches applying higher than usual energy levels for shorter periods (high power short duration, HPSD) to improve lesion quality have been reported. The novel DiamondTemp (DT) catheter allows for temperature-guided high power RFCA. Data on a direct comparison of the two emerging RFCA approaches are lacking. Purpose: This observational single center study aimed to compare the efficacy, safety and characteristics of the novel DT catheter to an ablation index (AI) guided 50 W high power short duration (HPSD) ablation protocol using a conventional force-sensing equipped ablation catheter with surround-flow. Methods: A total number of 101 patients undergoing RFA for AF were included. 33 patients treated with the DT catheter (50 W, 9 sec), were compared to 69 consecutive patients undergoing AI-guided AF ablation (AI anterior 550; AI posterior 400) with an open-irrigated catheter adherent to a 50 W HPSD protocol. Procedural data and recurrence rates were documented. Follow-up examinations were scheduled after 3, 6 and 12 months. Results: Acute procedural success was achieved in all patients (n=101, 100%). DT-guided AF ablation was associated with a significantly longer mean procedure duration (98.8±30.1min vs. 78.2±25.6, p=0.002*). PVI using the DT ablation catheter required significantly more RF applications (75.4±30.8min vs. 61.3±14.1, p=0.019*). Total RF duration was significantly lower in the DT group (792.1±311.2sec vs. 1035.5±287.2sec, p<0.001*) as well as fluoroscopy time (4.6±2.1min vs.5.5±2.5min, p<0.006*) and dose (183.8±178.1yGym2 vs. 295.8±247.5yGym2, p<0.013*). Procedure related mayor complications occurred in 1 patient from the DT group (acute stroke; 3%) and in no patients from the HPSD cohort. Early recurrence was reported from 4 patients treated with the DT catheter (12%) compared to 8 patients undergoing HPSD RFA (12 %) (p=1.000). Conclusion: Temperature- and power- controlled AF ablation using 50 W was safe and effective. AI-guided HPSD ablation resulted in significantly shorter procedure times with significantly fewer RF applications for PVI, whereas total RF duration and fluoroscopy times were significantly higher in this cohort. Further studies are needed to confirm this initial observation.